Use of Topography in the context of the GOCE satellite mission: some examples - Rexer, M.; Hirt, Christian; Claessens, Sten; Braitenberg, C.; Braitenberg, C. (European Space Agency, 2015)
The uppermost masses of the lithosphere - notably the land topography, bathymetry and ice - make a significant contribution to the gravity signal captured by ESA's GOCE gravity mission [1,2]. This circumstance is used 1) to evaluate ESA GOCE gravity field models of all generations, 2) to evaluate various topographic data sets and 3) to compute a global Bouguer gravity anomaly map. All of the above is facilitated through forward modelling of the ellipsoidal topographic potential (ETP) applying the Harmonic Combination Method [3]. Curtin University's new rock-equivalent topography (RET) model, taken from the Earth2014 suite of topographic data [4], serves as topographic input model for the gravity forward modelling. ESA GOCE models show steady improvement over time and prove to be sensitive for topographic gravity signals at scales of ~100 km and finer. Using the release-5 GOCE models as a reference, Curtin University's RET models are found to improve over time too. Finally, we demonstrate that the spectral representation of the ETP allows straightforward computation of global Bouguer anomaly maps.